Effects of short‐interval disturbances continue to accumulate, overwhelming variability in local resilience. Issue 3 (3rd March 2021) - Hayes, Katherine; Buma, Brian
Abstract: Increasing rates of short‐interval disturbances have the potential to rapidly transform ecosystems via shifts in post‐disturbance regeneration. While research has explored compound events in multiple biomes, we know little regarding how local site conditions interact with short‐interval disturbances to influence post‐disturbance regeneration. Furthermore, questions remain regarding the consequences of continued high frequency events: What happens when emerging new communities are themselves subject to short‐interval disturbances? To investigate effects of ongoing short‐interval fires on regeneration, we examined post‐fire forest regeneration in two locations in interior Alaska. We established 50 plots across a mosaic of fire histories (one, two, or three fires in <70 yr) in an upland and lowland site in interior Alaska. To investigate how shifts in community driven by short‐interval fires differ according to local site conditions, we quantified abundance, proportion, and density of conifer and deciduous regeneration in a drier upland site and a wetter lowland site. Both sites were dominated by black spruce prior to burning. In the drier upland site, black spruce ( Picea mariana ) presence declined sharply after two fires, while paper birch ( Betula neoalaskana ) became increasingly abundant with each additional fire. In the wetter lowland site, less organic soil was consumed by fire and presence of black spruce persisted through an initial single reburn (two fires), indicating local topography may temporarily buffer reburning impacts. However, after three burns, conifers were effectively eliminated in both upland and lowland stands. Deciduous regeneration differed with site: Birch dominated in upland plots, while willow ( Salix spp. ) and aspen ( Populus tremuloides ) dominated in lowlands. These results offer strong empirical evidence of the divergence of boreal successional trajectories from previous historic norms. Furthermore, results from this study demonstrate shifts in post‐fire succession in forested ecosystems continue to accumulate with additional short‐interval disturbance events, overwhelming the interactive effects of local site conditions.